Optimizing the Role of Stakeholders in the Agricultural Intended HIV/AIDS Management in Jember District: Optimalisasi Peran Stakeholder Dalam Penanggulangan HIV/AIDS Berwawasan Agrikultura di Kabupaten Jember - Kurniawan, Dicky Endrian; Purwandari, Retno; Afandi, Alfid Tri; Khamid, M. Nur (Al-Hijrah Indonesia, 2022)
One indicator of the effectiveness of HIV/AIDS prevention can be measured by the role of stakeholders involved in the HIV/AIDS prevention program. The obstacles are that there are still unequal perceptions of interest regarding the target group from each stakeholder in developing HIV/AIDS prevention programs and a lack of coordination between internal and external agencies, so there has been no effort to integrate programs between agencies. The purpose of this activity is to optimize the role of stakeholders in HIV AIDS prevention in Jember. This activity was carried out in stages (1) presenting material on